High Reintervention and Amputation Rates After Outpatient Atherectomy for Claudication. (August 2018) - Mukherjee, Dipankar; Contos, Brian; Emery, Erica; Collins, Devon T.; Black, James H.
Outpatient use of atherectomy for peripheral arterial disease has grown rapidly and outcomes are poorly understood. We analyzed outcomes of atherectomy done for claudication, comparing office and hospital outpatient settings. Analysis of Medicare Part B claims data was performed for incident femoral–popliteal or tibial–peroneal atherectomy from 2012 to 2014. Longitudinal analysis assessed services 18 months before, during, and up to 18 months after the incident peripheral vascular intervention (PVI). Differences between office-based and hospital outpatient-based settings were assessed using χ 2 and Fisher exact tests. Comparing procedure settings, significant differences in race (femoral–popliteal: P = .04, tibial–peroneal: P = .001), chronic renal failure (femoral–popliteal: P = .002), and hypertension (femoral–popliteal: P = .01, tibial–peroneal: P = .006) were found. Nine hundred twenty-four patients undergoing femoral–popliteal atherectomy were analyzed (262 office based, 662 hospital outpatient based); 42.7% of office-based and 36.9% of hospital outpatient-based femoral–popliteal atherectomy patients had repeat PVI within 18 months ( P = .10). Major amputation was performed in 2.3% and 3.2% of patients in office and hospital outpatient settings, respectively ( P = .47). Four hundred twenty-three patients undergoing tibial–peroneal atherectomy were analyzed (202 office based, 221 hospital outpatient based); 46.5% of office-based and 38.9% of hospital outpatient-based tibial–peroneal atherectomy patients had repeat PVI within 1 year ( P = .11). Major amputation was performed in 5.0% and 8.1% of patients in office and hospital outpatient settings, respectively ( P = .19). Our study demonstrates higher than expected rates of major amputation for patients undergoing peripheral arterial atherectomy with regard to previously reported rates. Further studies may be required to prove the efficacy and safety of atherectomy for occlusive disease in the femoral–popliteal and tibial–peroneal segments to ensure outcomes are not worse than the natural history of medically managed claudicants.